If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 4q = 17 + 3q Solving 12 + 4q = 17 + 3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3q' to each side of the equation. 12 + 4q + -3q = 17 + 3q + -3q Combine like terms: 4q + -3q = 1q 12 + 1q = 17 + 3q + -3q Combine like terms: 3q + -3q = 0 12 + 1q = 17 + 0 12 + 1q = 17 Add '-12' to each side of the equation. 12 + -12 + 1q = 17 + -12 Combine like terms: 12 + -12 = 0 0 + 1q = 17 + -12 1q = 17 + -12 Combine like terms: 17 + -12 = 5 1q = 5 Divide each side by '1'. q = 5 Simplifying q = 5
| 51=3+8x | | U=might | | Ak-r=an | | 24/-10-5/-4 | | 3(7+2)=3(7)+3(2) | | 2z^2+9z=5 | | 1.8x+2.8=2.5x+2 | | 4(x+3)-4=8x+10-4 | | 3x+5=4x-6 | | 3.2/3.44 | | 3(x-2)=5x-2x-6 | | m/7=3/5 | | -x-(13+4x)=-3(6-9x)+2 | | w=-10.5+0.5p | | 5m-13m=16 | | 1/3*3.14*4*4*7 | | 9x-2(x-8)=7(x+1)+6 | | 3x-2(x+3)=5x-2x | | Lw=a | | 6-g=2 | | 7-y=3 | | 4x-10y=2+10 | | 3(P-1)=2p+3 | | 3/q=1 | | 8+4x=11+x | | 4+12=-30-10x | | Xy+7y=17 | | Xy+7y= | | x+22.6=84.6 | | 9x-2(x-8)=(x+1)+6 | | x^3+9x^2+18x+28=0 | | 3(m+1.5)=1.5(2m+5) |